ANALISIS PELAKSANAAN SELF ASSESSMENT SYSTEM DAN KEPATUHAN WAJIB PAJAK BADAN DALAM RANGKA MENINGKATKAN PENERIMAAN PAJAK PADA KANTOR PELAYANAN PAJAK BEKASI BARAT - Fadlun Nisa; Siti Nurlatifah (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2019)
During the last three years, namely in 2015 until 2017 the government revenue from the tax sector in West Bekasi KPP Pratama did not reach the target, the tax target that has been determined annually is not achieved, even though all efforts have been made to reach the target predetermined tax. But the obstacles encountered were also not small, including decreasing taxpayer compliance and the weakening of the economy in Indonesia. The level of implementation of the Self Assessment System and Compliance of Corporate Taxpayers at KPP Pratama Bekasi Barat can be said to be less effective and less compliant, this is because there are still many Corporate Taxpayers who are less concerned about taxes. It is shown from the number of effective corporate taxpayers which decreases annually, besides that there are still many corporate taxpayers who do not understand how to fill SPT properly, correctly, completely and do not know about the applicable tax rates, still there are also many corporate taxpayers who do not update about taxes so there are still many taxpayers who do not know about the deadline for payment, delivery, and tax reporting. All of this indicates that the corporate taxpayer's compliance in KPP Pratama Bekasi Barat declined. Of course this has an effect on tax revenue at KPP Pratama Bekasi Barat.